1996
DOI: 10.1289/ehp.961041339
|View full text |Cite
|
Sign up to set email alerts
|

An expanded cohort study of cancer among benzene-exposed workers in China. Benzene Study Group.

Abstract: An expanded cohort study of 74,828 benzene-exposed and 35,805 unexposed workers were followed during 1972 to 1987, based on a previous study in 12 cities in China. A small increase was observed in total cancer mortality among benzene-exposed compared with unexposed workers (relative risk [RR] = 1.2). Statistically significant excesses were noted for leukemia (RR = 2.3), malignant lymphoma (RR = 4.5), and lung cancer (RR = 1.4). When risks were evaluated by leukemia subtype, only acute myelogenous leukemia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 19 publications
0
39
1
Order By: Relevance
“…A follow-up survey of 28,460 benzene-exposed and 28,257 unexposed workers from 1972 through 1981 found an increased risk of mortality due to leukemia [standardized mortality ratio (SMR) = 5.7] (123). In 1987, the U.S. National Cancer Institute (NCI) began collaborating with the CAPM team to identify all incident cases of hematologic neoplasms and related disorders in an expanded study cohort of 74,828 benzene-exposed and 35,805 unexposed workers employed from 1972 through 1987 in 12 cities in China (37, 122). The study confirmed increased risks of acute myeloid leukemia (AML) and other malignant and non-malignant hematopoietic disorders associated with benzene exposure and found evidence for hematopoietic cancer risks at levels substantially lower than had previously been established.…”
Section: Traditional Epidemiological Studies Of the Carcinogenic Effementioning
confidence: 99%
“…A follow-up survey of 28,460 benzene-exposed and 28,257 unexposed workers from 1972 through 1981 found an increased risk of mortality due to leukemia [standardized mortality ratio (SMR) = 5.7] (123). In 1987, the U.S. National Cancer Institute (NCI) began collaborating with the CAPM team to identify all incident cases of hematologic neoplasms and related disorders in an expanded study cohort of 74,828 benzene-exposed and 35,805 unexposed workers employed from 1972 through 1987 in 12 cities in China (37, 122). The study confirmed increased risks of acute myeloid leukemia (AML) and other malignant and non-malignant hematopoietic disorders associated with benzene exposure and found evidence for hematopoietic cancer risks at levels substantially lower than had previously been established.…”
Section: Traditional Epidemiological Studies Of the Carcinogenic Effementioning
confidence: 99%
“…In reviewing the literature, however, there are no in vivo studies related to the effects of benzene exposure on lung cell apoptosis. Yet animal studies have shown that the lung is a target organ of benzene tumorigenicity, while human subjects exhibit increased risks for adenocarcinoma and squamous cell carcinoma of the lung when occupationally exposed to benzene (Aksoy, 1989;Yin et al, 1989Yin et al, , 1996aHayes et al, 1996) as well as to cigarette smoke (Darrall et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Better integration of these disciplines will lead to stronger study designs, for example, by reducing the common occurrence of occupational cohorts that include women but fail to report data for breast cancer even though they are studying exposures to chemicals that cause mammary gland tumors. [6][7][8][9] Second, we seek to strengthen the practice of toxicology, including animal testing and risk assessment, as a tool for breast cancer prevention. Focusing on the mammary tumor endpoint may identify ways to strengthen chemical screening and testing, and improve interpretation of data from these tests in order to maximize the relevance to human breast cancer.…”
mentioning
confidence: 99%